FEATURES OF TEACHING THE SUBJECT " RUSSIAN LANGUAGE AND CULTURE OF SPEECH "AT THE AGRICULTURAL UNIVERSITY (Academicia Globe: Inderscience Research, 2023)
This article provides information on the features of teaching the subject "Russian language and culture of speech" at an Agricultural University.